2004
DOI: 10.1161/01.hyp.0000140924.91479.03
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cyclooxygenase-2 in the Rat Renal Medulla Leads to Sodium-Sensitive Hypertension

Abstract: Abstract-Cyclooxygenase-2 expression in the renal medulla is regulated by dietary salt intake. The present study was performed to determine the influence of chronic inhibition of medullary cyclooxygenase-2 on arterial blood pressure in conscious Sprague-Dawley rats maintained on a high-salt (4% NaCl) or a low-salt (0.4% NaCl) diet. Rats were uninephrectomized and instrumented with femoral arterial and femoral vein or renal medullary interstitial catheters. Each rat received a continuous medullary or intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
65
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 44 publications
6
65
0
Order By: Relevance
“…Increases in medullary COX-2 expression in response to salt loading were also markedly blunted in ptAadc -/-mice. COX-2-derived prostaglandins are important integrators of vascular tone and salt and water homeostasis in the renal medulla, and inhibition of medullary COX-2 activity can lead to hypertension (17,(22)(23)(24)(25). These results therefore confirm those of previous studies that suggested a potential role for dopamine to increase pronatriuretic renal medullary prostaglandin production (26,27).…”
Section: Figuresupporting
confidence: 88%
“…Increases in medullary COX-2 expression in response to salt loading were also markedly blunted in ptAadc -/-mice. COX-2-derived prostaglandins are important integrators of vascular tone and salt and water homeostasis in the renal medulla, and inhibition of medullary COX-2 activity can lead to hypertension (17,(22)(23)(24)(25). These results therefore confirm those of previous studies that suggested a potential role for dopamine to increase pronatriuretic renal medullary prostaglandin production (26,27).…”
Section: Figuresupporting
confidence: 88%
“…For example, the COX-2 enzyme pathway has been found to be upregulated in response to high-salt intake apparently via an NF-B pathway, resulting in increased synthesis of PGE 2 (26,69,105,122,198,200,205,207). Specific inhibition of COX-2 in the renal medulla acutely reduces sodium excretion and when inhibited chronically produces salt-sensitive hypertension in SD rats (104,105,122,183,199,207). This is not the case with COX-1, which is constitutively expressed in the medullary collecting ducts and interstitial cells and is not altered by a salt diet (200).…”
Section: Medullary O 2 ·ϫ No and H 2 O 2 As Determinants Of Blood mentioning
confidence: 99%
“…Increases in the expression of renal medullary COX-2, but not COX-1, are seen in response to chronic salt loading (8,15,40). Emerging evidence suggests that renal medullary COX-2 may play a role in the promotion of sodium excretion and, thereby, the stabilization of BP (41). Major goals of the present study are as follows: 1) to resolve cellular localization of high-saltinduced COX-2 expression in the renal medulla, 2) to provide further evidence for the antihypertensive function of renal medullary COX-2 with use of chronic infusion and telemetry techniques, and 3) to examine the potential role of renal medullary COX-1 in BP regulation.…”
mentioning
confidence: 99%